Sleep patterns among Norwegian nurses between the first and second wave of the COVID-19 pandemic - Siri Waage; Ståle Pallesen; Øystein Vedaa; Hogne Buchvold; Kjersti Marie Blytt; Anette Harris; Bjørn Bjorvatn (BMC, 2021)
Abstract Background Nurses are in the frontline and play an important role in the battle against the COrona VIrus Disease-2019 (COVID-19) pandemic. Sleep problems among health care workers are likely to increase due to the pandemic. However, it is conceivable that negative health outcomes related to the pandemic fluctuate with the infection rate waves of the pandemic. The present study aimed to investigate sleep patterns among Norwegian nurses, after the first wave, during a period with very low rates of COVID-19. Methods Data stemmed from the cohort study "SUrvey of Shift work, Sleep and Health (SUSSH)" among Norwegian nurses. A total of 1532 nurses responded one time to a questionnaire between June and September in 2020 including items about demographics and work, information about COVID-19 and quarantine, sleep patterns and changes in sleep patterns due to the pandemic. Descriptive statistics for all relevant variables were calculated and McNemar tests were used to compare categorical variables. Results The majority of nurses (84.2%) reported no change in sleep duration after the first wave of the COVID-19 pandemic compared to before, 11.9% reported less sleep, and 3.9% reported more sleep. Similarly, 82.4% of the nurses reported no change in their sleep quality, whereas 16.2% of the nurses reported poorer sleep quality after the first wave of the pandemic compared to before. The majority of nurses reported no change in their sleep schedule due to the pandemic, although 9.6% of the nurses reported to go to bed later and 9.0% woke up earlier than before the pandemic. Conclusions Most existing literature exploring sleep among health care workers during the COVID-19 pandemic has been carried out during periods with high infection rates. In this study we aimed to investigate sleep patterns among Norwegian nurses following the first wave, during a period of low COVID-19 rates in Norway. Most of the nurses reported no change in neither sleep duration, sleep quality, bedtime, nor wake-up times compared to before the pandemic. Still, nearly 12% reported shorter sleep duration, and about 16% reported poorer sleep quality indicating that some nurses experienced worsening of their sleep following the pandemic.